2020
DOI: 10.1371/journal.pone.0232382
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and antibiotic resistance of Salmonella spp. in South Punjab-Pakistan

Abstract: Present study aimed at investigating the magnitude of the prevalence and antibiotic resistance among four Salmonella spp. i.e., S. typhi, S. paratyphi A, S. paratyphi B and S. typhimurium. Raw milk and environment samples were collected from the five districts of southern part of the province of Punjab in Pakistan i.e., Multan, Bahawalpur, Lodhran, Dera Ghazi Khan and Muzaffargarh. Extent of antibiotic resistance was also determined and classified as resistant, intermediate and susceptible. District–wise preva… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 34 publications
3
14
0
Order By: Relevance
“…However, such use has been associated with the development of resistance by bacteria. Resistance to various antimicrobials by Salmonella has been reported in Pakistan, 7 Ghana, 8 and Ethiopia. 9 The misuse of antimicrobials in humans and animals has led to an increase in the number of multidrug-resistant bacterial strains, which has been identified by WHO and health authorities as a global public health and veterinary concern.…”
Section: Introductionmentioning
confidence: 99%
“…However, such use has been associated with the development of resistance by bacteria. Resistance to various antimicrobials by Salmonella has been reported in Pakistan, 7 Ghana, 8 and Ethiopia. 9 The misuse of antimicrobials in humans and animals has led to an increase in the number of multidrug-resistant bacterial strains, which has been identified by WHO and health authorities as a global public health and veterinary concern.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between sensitivity and resistance patterns has also been studied previously [6]. One previous study used the double disc synergy test that verified the phenotypic resistance, which was the legitimate cause of the development of resistance to commercially available antibiotics [25]. The findings from previous studies indicated that heavy metal rates, which were elevated in the river tyne basin as a consequence of earlier industrial and mining activities, were related to the high rates of AMR [29,30].…”
Section: Discussionmentioning
confidence: 98%
“…Antibiotic susceptibility and identification of the AMR agents implicated in the human body are critical for empirical treatment and the escaping of resistant bacteria [24]. Qamar et al (2020) documented that antibiotics have enabled great advancements in healthcare systems, but they are under threat from rapidly evolving resistant microbes [25]. Only a few studies have been conducted in Pakistan to check the prevalence of metal-resistant bacteria and the antimicrobial sensitivity profiles of those bacteria [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…18 Recent data from South Punjab Pakistan has shown high rates of resistance shown by salmonella typhi against Oxytetracycline (70.1%) while Ofloxacin (90.4%) and Cefepime (89.7%) had the highest sensitivity. 19 …”
Section: Discussionmentioning
confidence: 99%